Investigation of CO2 and methanol solubility at high pressure and temperature in the ionic liquid [EMIM][BF4] employed during methanol synthesis in a membrane-contactor reactor. (12th October 2021) - Zebarjad, Fatemeh Sadat; Wang, Zi; Li, Hao; Hu, Sheng; Tang, Yongchun; Tsotsis, Theodore T.
Graphical abstract: Highlights: Experimental solubility data for CO2 and MeOH in [EMIM][BF4 ] IL. Validated the applicability of [EMIM][BF4 ] as sweep solvent in the MR-MeS process. At MeS temperature condition (220 °C), CO2 solubility in [EMIM][BF4 ] is negligible. IL showed higher MeOH solubility compared to TGDE at all temperatures studied. IL solubility properties remain unchanged during the MR-MeS experiments. Abstract: In this paper, the solubility properties of the ionic liquid (IL), 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF4 ]) were studied using a high-pressure, high-temperature set-up employing the pressure-drop technique. [EMIM][BF4 ] was selected because it is used as sweep liquid in a membrane reactor (MR)-based methanol synthesis (MR-MeS) process recently proposed/studied by our group. The MR-MeS studies indicated high methanol (MeOH) solubilities in the IL under typical MeS reaction conditions, which then motivated this study to measure such solubilities directly under non-reactive conditions to validate the MR study findings. In addition, during the MR-MeS studies concerns existed about the CO2 solubility in [EMIM][BF4 ], since it is a reactant and its dissolution in the IL would be detrimental for performance. Studies, therefore, were also carried out to investigate CO2, in addition to MeOH solubility. Our investigation indicates that though CO2 solubilities are high at room temperature, they become negligible at the typical MeS conditions.